TEACHER'S PNBE: READING TRAINING, READING IN THE PROFESSION: THAT IS THE QUESTION! - Brandao, Claudia Leite [UNESP]; Pilegi Rodrigues, Silvia de Fatima (Univ Estadual Sudoeste Bahia, 2019)
The purpose of this text is to analyze the distribution of theoretical and methodological books for public schools by Professor PNBE (PNBE do Professor) for the years 2010 and 2013. For this, we start with a qualitative approach, with bibliographical research about some concepts of reading, the understanding of the Teacher's PNBE and a case study carried out in the city of Primavera do Leste - Mato Grosso, in the period from 2014 to 2016, with thirty (30) teachers from the state network to address the (dis) knowledge of distributed works by the Program. The results indicated that the distribution of the teacher's PNBE collections was made, but teachers were still unaware of the arrival of these materials in educational establishments. This finding led us to understand the importance of implementing actions within school units to promote the dissemination of materials among education professionals, as well as the articulation of the teacher's PNBE materials with the teacher training programs.
Keywords: Formation of the reader; Teacher's PNBE; Policies for reading; Teacher-reading